Baseline Hematologic Reserve and Laboratory-Defined Leukopenia/Neutropenia During Vancomycin Therapy: A Real-World Risk-Stratification Cohort Study - Dong Wu; Xiaowu Wang; Changjing Chen; Xiaoying Wang; Hao Li; Linlin Zhao; Guangli Li; Xiaojuan Wang (Annals of Pharmacotherapy, 2026)
Background: Laboratory-defined leukopenia/neutropenia may occur during vancomycin therapy, but mild threshold-crossing abnormalities do not necessarily establish definite drug-induced toxicity. Objective: To develop and evaluate a risk-stratification strategy based on baseline hematologic reserve and vancomycin treatment duration. Methods: This single-center retrospective cohort included adult inpatients receiving intravenous vancomycin for ≥3 days. Patients with baseline leukopenia/neutropenia, hematologic disease, malignancy or antitumor therapy, non-intravenous use, or unavailable blood counts were excluded. The primary endpoint was laboratory-defined leukopenia/neutropenia, defined as new white blood cell count (WBC) 14 days, with an event rate of 75.0%. The baseline score model showed moderate performance (area under the curve [AUC] 0.697), whereas the extended model incorporating the score-defined risk group, treatment duration, and clinical covariates improved discrimination (AUC 0.786). Conclusion and Relevance: A 4-component baseline hematologic reserve score combined with treatment duration may help identify patients who warrant closer complete blood count monitoring during vancomycin therapy. These findings should be interpreted as laboratory-event risk stratification rather than proof of definite vancomycin-induced toxicity or as a mandatory discontinuation threshold.